Impacto da Pandemia COVID-19 na Saúde Mental dos Anestesiologistas do Sistema de Saúde Nacional - Tiago, Catarina (2020)
Introduction: The coronavirus disease (COVID-19) pandemic has posed strain on the entire healthcare system. Portuguese anaesthesiologists played a major role, being relocated to newly created intensive care units and performing risky procedures such as endotracheal intubation. We aimed to evaluate how the COVID-19 pandemic affected the mental health of Portuguese Anaesthesiologists working for the National Health Service. Materials and Methods: Transversal observational descriptive and analytical study directed to residents and specialists in Anaesthesiology working in public hospitals in Portugal during the COVID-19 pandemic. We used the 12-item General Health Questionnaire (GHQ-12). Mann-Whitney and ANOVA or Kruskal-Wallis tests were used to compare the GHQ-12 score between groups and paired sample t-test to compare the GHQ-12 score before and during the pandemic. The statistical significance was considered for p-value < 0.05. Results: 184 physicians answered the questionnaire. The majority of the respondents were women (75%) and most participants were aged between 31 and 40 years old (31%). Participants were mainly from the Northern Region (55.4%). Female participants presented a statistically significant higher GHQ-12 score (p-value 0.024). Nearly 80% of the participants exhibited psychological distress during the pandemic. The main adversities faced were fear of infecting the family and lack of hospital organization. Discussion and Conclusions: Participants reported experiencing a higher psychological burden during the COVID-19 pandemic, especially women. Therefore, it is important to recognize this problem and take measures to improve the mental health of Anesthesiologists and other healthcare workers to avoid potential short and long-term consequences.